Hubungan Tingkat Stres Kerja Perawat dengan Kualitas Tidur pada Perawat di RS Medika Lestari - Ekberth Mandaku; Harun Wahyudi; Merri Silaban (Jurnal Siti Rufaidah, 2024)
Nurses play a crucial role in healthcare systems but often face work stress due to heavy workloads, high responsibilities, and irregular schedules. Excessive work stress can impair sleep quality, affecting nurses' physical and mental health and patient care quality. Preliminary data at RS Medika Lestari showed that many nurses experienced moderate to severe work stress and poor sleep quality. This study aims to analyze the relationship between work stress levels and sleep quality among nurses at RS Medika Lestari in 2024. The research design used was descriptive-correlational with a cross-sectional approach. A total of 42 nurses were selected as samples through cluster random sampling. Work stress levels were measured using the DASS 42 questionnaire, and sleep quality was assessed using the PSQI. The analysis revealed a significant positive relationship between work stress levels and sleep quality (r = 0.594; p = 0.000). Most nurses experienced moderate work stress (40.5%) and poor sleep quality (69%). This study highlights the importance of stress management programs and improved working conditions to enhance nurses' sleep quality and overall well-being.